Veterinary vaccines principles and applications - Metwally, Samia; El Idrissi, Ahmed; Viljoen, Gerrit J. (Hoboken, NJ Wiley-Blackwell, 2021)
"Veterinary Vaccines: Principles and Applications is a concise and authoritative reference on the use of vaccines against diseases of livestock. Compiled by Animal Health Officers at the UN-FAO and with contributions from international experts, the text comprises easily readable reviews of the latest research in vaccinology and vaccine immune response to pathogens of major economic impact to livestock"--
The role of veterinary vaccines in livestock production, animal health and public health -- Principles of vaccinology and vaccine immune response -- Role of the regional and international organizations in vaccine international standards -- Vaccination strategies, implementation and monitoring -- Viral vaccines -- Bacterial and mycoplasma vaccines -- Protozoal and rickettsial vaccines -- Parasite vaccines -- Fish vaccines -- Novel developments and next generation vaccines -- The manufacture of veterinary vaccines : manufacturing facilities -- The manufacture of veterinary vaccines : quality control of the manufacturing processes -- The manufacture of veterinary vaccines : control of final product -- The manufacture of veterinary vaccines : external assessment and registration of veterinary vaccines -- Aspects of vaccine accessibility and commercialization -- Vaccine strategic reserves -- Foot and mouth disease -- Avian influenza -- Rift Valley Fever -- Bluetongue -- Peste des Petits Ruminants -- Brucellosis -- Contagious Bovine Pleuropneumonia -- Classical Swine Fever -- Newcastle disease virus -- Porcine Reproductive and Respiratory Syndrome -- Anthrax -- Capripox (lumpy skin disease & sheep and goat pox) -- Rabies.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Livestock; Vaccines; Veterinary vaccines; Poultry; Vaccination of animals